2016
DOI: 10.1097/ede.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Excluding Treatments in Network Meta-analysis

Abstract: Network meta-analysis (NMA) of randomized controlled trials is increasingly used to combine both direct evidence comparing treatments within trials and indirect evidence comparing treatments across different trials. When the outcome is binary, the commonly used contrast-based NMA methods focus on relative treatment effects such as odds ratios comparing two treatments. As shown in a recent report, when using contrast-based NMA, the impact of excluding a treatment in the network can be substantial, suggesting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…The impact of exclusion of treatments arms was investigated in Mills et al [8] and Lin et al [9] empirically and substantial influence was found, whereas the impact of exclusion of trials has not been explored before. In this paper we empirically studied this impact using 20 published networks and documented that exclusion of trials can sometimes affect the estimation of treatment effects substantially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of exclusion of treatments arms was investigated in Mills et al [8] and Lin et al [9] empirically and substantial influence was found, whereas the impact of exclusion of trials has not been explored before. In this paper we empirically studied this impact using 20 published networks and documented that exclusion of trials can sometimes affect the estimation of treatment effects substantially.…”
Section: Discussionmentioning
confidence: 99%
“…They consequently stated that selection of treatment arms should be carefully considered when applying NMAs. Another publication by Lin et al [9] further explored the sensitivity to excluding treatments using both the armed-based (AB) [1] and contrast-based (CB) [2] NMA approaches. They found that when a treatment was removed under the CB framework, it was also necessary to exclude the other treatment in two-arm studies that investigated the excluded treatment, while such additional exclusions were not necessary in the AB framework.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the arm-based method can use information contained in single-arm studies, in which only one treatment group is available or of interest. Single-arm studies cannot be included in the contrast-based model but they may provide valuable information for treatment comparisons and enhance the robustness of a network meta-analysis (Lin et al 2016a). Although the arm-based approach has many advantages, the convergence of Markov chain Monte Carlo (MCMC) algorithms for parameter estimation may be slower compared with the contrast-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The multivariate meta-analysis models have been applied to several areas, such as metaanalysis of diagnostic tests, [16][17][18] meta-analysis of multiple outcomes, 19,20 and network meta-analysis of mixed treatment comparisons. [21][22][23][24][25][26] Mixed treatment comparisons use both direct and indirect evidence of treatment contrasts to synthesize the comparisons between multiple treatments; its focus differs from MVMA-MF, because MVMA-MF is interested in estimating the effect of multiple factors, not the contrasts between them.…”
Section: Introductionmentioning
confidence: 99%